THE EFFECT OF HEALTH EDUCATION BY THE ROLE PLAY METHOD ON KNOWLEDGE LEVEL ABOUT PREVENTION OF SEXUAL VIOLENCE IN SCHOOL AGES - Meilinda Ulfah Adha Suhenda; Tetti Solehati; Ai Mardhiyah (Journal of Maternity Care and Reproductive Health, 2019)
Cases of child sexual violence (KSA) in Bandung Regency continue to increase, and cause physical, psychological, growth, development and traits in the future. KSA prevention education is needed as primary prevention to increase children's knowledge in order to protect themselves. This study aimed to analyze the effect of education through the role play method on the level of knowledge regarding the prevention of school-age KSA in Solokan Garut Elementary School, Bandung Regency. This type of research was Pre-Experimental with One group pre and post-test design. Sample selection used purposive sampling techniques. The study involved 47 respondents from grade 1 and 2 students at Solokan Garut Elementary School in Bandung Regency. The treatment in the form of education to prevent KSA at school age uses the "TANGKIS" jargon with the role play method. The instrument used a modification of the "TANGKIS" material questionnaire and early age education journal that has done face validity and instrument testing with valid and reliable results 0.87. Data were analyzed using univariate analysis of frequency distribution and percentage, and bivariate analysis of the Wilcoxon test. The results showed an increase in children's knowledge when the Pre-test was 34 children in good category (72.3%) and increased when the Post-test as many as 38 children in the good category (80.9%). In bivariate analysis, there was a p-value of 0.016. The conclusion of this study is that there are significant differences in the level of knowledge of school-age children before and after being given education through role play regarding prevention of KSA in Solokan Garut Elementary School, Bandung Regency. The advice of this study is to apply this method regularly and develop other educational methods that are suitable and effective for adolescents.Keywords: Education, Knowledge, Prevention of sexual violence, School-age children.